PERANAN MOTIVASI KERJA DALAM MENINGKATKAN KINERJA APARATUR PEMERINTAHAN DESA SIPODECENG - Suparman Suparman; Muhammad Rohady Ramadhan; Herman Dema; Muhammad Rais Rahmat Razak; Aman Darmawan (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2026)
This study analyzes the work motivation of Sipodeceng Village government apparatus and the factors affecting public service performance. Unlike previous predominantly quantitative research, this study employs a phenomenological qualitative approach to explore the subjective experiences of village apparatus in understanding their work motivation. Data were collected through in-depth interviews with 8 informants (Village Head, Village Secretary, 2 Hamlet Heads, and 4 village staff), observation, and documentation, then analyzed using NVivo 12 Plus with data validity techniques including source triangulation, method triangulation, and member checking. Results show that work motivation is formed through a combination of intrinsic motivation (responsibility, pride in serving) dominant at leadership levels, and extrinsic motivation (work facilities, allowances) that more significantly influences implementing staff. Findings confirm Self-Determination Theory and Herzberg's Two-Factor Theory, while revealing new dimensions such as local identity-based motivation and the role of paternalistic leadership. Apparatus performance improves through balanced intrinsic-extrinsic factors, supportive work environment, and responsive leadership. Practical implications include the need for performance-based recognition systems, continuous technology training, improved work facilities, and fair remuneration policies at village government level.